Rent Seeking and Endogenous Income Inequality - Wade, Paul.; Dabla-Norris, Era. (Washington, D.C. : International Monetary Fund, 2001)
This paper studies the relationship between wealth inequality and occupational choice between rent-seeking and production. With imperfect credit markets and a fixed cost to rent-seeking, only wealthy agents choose to engage in rent-seeking as it enables them to protect their wealth from expropriation. Hence, initial wealth determines occupational choice and aggregate economic activity. The model also generates an unequal wealth distribution endogenously through fair gambles undertaken voluntarily, despite agents being identical ex ante. If agents have an altruistic bequest motive, income and occupational differences can be perpetuated from generation to generation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet